Connor Kenway’s Search for Freedom as An American Indian in the Video Game Assassin’s Creed III - Adelbertus Hugo; Hirmawan Wijanarka (Journal of Language and Literature, 2024)
This study focuses on Connor Kenway's struggles seeking freedom as an American Indian in the game Assassin's Creed III (2012). Three problems will be examined in the video game: the portrayal of Connor, Connor's struggle with the colonizer in his search for freedom, and the meaning of freedom for Connor as an American Indian. This study is library research using a post-colonial perspective. Three theories are applied to answer the research problems: the theory of characterization, the theory of post-colonialism, and the theory of freedom. The theory characterization is applied when analyzing the portrayal of Connor in the video game. Post-colonial theory is referred to when examining the power dynamics and inequalities that emerge when one culture or nation subjugates another, which later causes Connor to struggle. The theory of freedom is the reference when describing the meaning of freedom for Connor. The results of this study show that Connor is portrayed as an ambitious, fearless, skilled, loyal, dedicated, and stubborn figure. Connor's struggles start when he first becomes an Assassin, meets his mentor, carries out various missions against the colonial, and even kills his father, who has different views on freedom from him. For Connor, freedom is more than just political independence. It is about the right to live according to one's values and traditions, creating a more just and equitable society, and recognizing the freedom of all peoples, not just one particular group or nation.